Don't tell me stories: The narratives of retirement and their relation with brand associations - Monika Hajdas; Joanna Radomska; Aleksandra Szpulak; Susana C. Silva (International Journal of Management and Economics, 2022)
Purpose: The concept of cultural branding based on various narratives has been established in the marketing literature, but there is a lack of studies linking this concept with brand-related effects. The aim of this paper is to explore and explain the possible relationships between various brand narratives based on the changing meaning of retirement and brand associations. Design/methodology/approach: An experimental design was used to test the proposed conceptual model and examine the impact of brand narrative on brand associations. Data were collected using an online survey from a random group of 432 respondents and analyzed using MANOVA. Findings: Our research did not confirm that in the case of financial products, brand narratives represented by distinctive retirement cultural codes had an impact on brand associations. Partial relation was found only for brand personality. Originality: This is the first study that explores brand narratives' based on cultural codes relations with brand associations.
Keywords: M31; M37; 650; brand associations; brand narrative; cultural branding; cultural codes; retirement